A report of a galactan from marine alga Gelidium crinale with in vivo anti‐inflammatory and antinociceptive effects. (24th October 2011) - de Sousa, Albertina A.S.; Benevides, Norma M.B.; de Freitas Pires, Alana; Fiúza, Felipe P.; Queiroz, Maria G.R.; Morais, Thamires M.F.; Pereira, Maria G.; Assreuy, Ana M.S.
Abstract The sulfated galactan of the red marine alga Gelidium crinale (SG‐Gc) was purified by ion exchange chromatography and tested by intravenous (i.v.) route in rodent experimental models of inflammation and nociception. The anti‐inflammatory activity of SG‐Gc (0.01, 0.1 and 1 mg/kg) was evaluated in the model of rat paw edema induced by different inflammatory stimuli, while SG‐Gc (0.1, 1 and 10 mg/kg) antinociceptive effect was assessed in models of nociception/hyperalgesia elicited by chemical (formalin test), thermal (hot plate), and mechanical (von Frey) stimuli in mice. In addition, the toxicity was evaluated after rat treatment with SG‐Gc (1 mg/kg; i.v.) during 10 days, followed by analysis of the wet weight of animal's body/organs and hematological/biochemical parameters. Sulfated galactan of G. crinale inhibited the time course of dextran‐induced paw edema, at all doses, showing maximal effect at 1 mg/kg (42%) and that induced by carrageenan at 0.01 (18%) and 1 mg/kg (20%), but was ineffective on the edema elicited by zymosan. At the highest dose, SG‐Gc also inhibited the paw edema induced by histamine (49%), compound 48/80 (32%), and phospholipase A2 (44%). Sulfated galactan of G. crinale inhibited both neurogenic and inflammatory phases of the formalin test, at all doses, and at 10 mg/kg, the animals flinch reaction in the von Frey test in the 1st and 3rd h by 19 and 26%, respectively. Additionally, SG‐Gc treatment was well tolerated by animals. In conclusion, SG‐Gc presents anti‐inflammatory effect involving the inhibition of histamine and arachidonic acid metabolites and also antinociceptive activity, especially the inflammatory pain with participation of the opioid system.